The final problem : a novel - Pérez-Reverte, Arturo (Mulholland Books/Little, Brown and Company, 2026)
"In this locked-room mystery set in 1960, a washed-up actor puts his on-camera detective skills to the test when a suspicious death shatters the quiet peace for a group of strangers staying at an isolated Greek island resort. June, 1960. Rough weather at sea leaves a group of strangers stranded on the idyllic Greek island of Utakos, all guests of the only local hotel. Nothing could prepare them for what happens next: Edith Mander, a quiet British tourist, is found dead inside a beach cabana. What appears at first glance to be a clear suicide reveals possible signs of foul play to Ormond Basil, an out-of-work but still well-known actor who in his glory days portrayed the most celebrated detective of all time. Accustomed to seeing him display Sherlock Holmes' amazing powers of deduction on the big screen, the other guests believe that the actor is the best equipped to uncover the truth. But when a second body is discovered, there is not a doubt in Basil's mind: a murderer walks among them. What's more, the killer is staging each crime as a performance, leaving complex clues that bear an eerie resemblance to those found in the pages of Conan Doyle stories. This is a criminal who knows every trick in the book and is playing a deadly literary game. As the storm rages, Basil must become the genius detective he has only pretended to be"--